Nutritional value and physicochemical composition of pearl millet (Pennisetum glaucum) produced in Benin., - ADEOTI, ADEOLA ZOURI-KIFOULI; Kouhoundé, Sonagnon H.S.; Noumavo, Agossou Daniel Pacôme; BABA-MOUSSA, FARID; TOUKOUROU, FATIOU (My University, 2017)
The high prices of animal foods and limited income earned in developing countries have resulted in their dependency on cereal-based preparations as staple food. Cereals such as maize, sorghum or pearl millet are often used in the production of various traditional foods and beverages in many African countries including Benin. In the republic of Benin, the nutritive value of cereals such as maize and sorghum is well documented. However, the nutritional value of pearl millet varieties produced in Benin remains to be investigated. The aim of this study was to assess the nutritional value of 22 varieties of pearl millet produced in Benin. After samples collection, the pearl millet grains were milled into fine powder and their compositions in six minerals (Na+, K+, Ca2+, Mg2+, Fe2+, Zn2+) and proximate (ash, dry matter, starch, protein, total and reducing sugars) were determined using standard analytical AOAC methods. Next, we assessed the relationship between these variables using the Pearson Correlation Analysis (PCA). We found that protein, total and reducing sugars levels varied widely (ranged from 1.86 to 93.4 mg/g, 178.64 to 652.54 mg/g and 16.62 to 174.22 mg/g, respectively). Additionally, we found a highly significant correlation (P<0.001) between levels of starch and amylose. Mineral levels also varied widely, with some millet cultivars being particularly enriched in iron and magnesium (levels ranged from 13.85 to 2766.31 mg/kg, and from 340.27 to 4769.9 mg/kg, respectively). Four groups of pearl millet can be distinguished based on data from the PCA: iron-rich millets (group G1), carbohydrate-rich millets (group G2), and two less nutritious millets (groups G3 and G4). This study opens new avenues for millet fortification and provides opportunity to increase farmers’ awareness in selecting pearl millet varieties for reducing malnutrition.
Keywords: Pearl millet; nutritional value; physicochemical composition; food security; Benin